Tackling bioactive glass excessive in vitro bioreactivity: preconditioning approaches for cell culture tests - Ciraldo, Francesca E.; Westhauser, Fabian (Acta biomaterialia, 2018)
Bioactive glasses (BGs) are being increasingly considered for biomedical applications in bone and soft tissue replacement approaches thanks to their ability to form strong bonding with tissues. However, due to their high reactivity once in contact with water-based solutions BGs rapidly exchange ions with the surrounding environment leading in most cases to an undesired increase of the pH under static in vitro conditions (due to alkaline ion “burst release”), making difficult or even impossible to perform cell culture studies. Several pre-conditioning treatments have been therefore proposed in laboratories worldwide to limit this problem. This paper presents an overview of the different strategies that have been put forward to pre-treat BG samples to tackle the pH raise issue in order to enable cell biology studies. The paper also discusses the relevant criteria that determine the selection of the optimal pre-treatment depending on the BG composition and morphology (e.g. particles, scaffolds). - Statement of Significance - Bioactive glasses (BGs), since their discovery in 1971 by L.L Hench, have been widely used for bone replacement and repair, and, more recently, they are becoming highly attractive for bone and soft tissue engineering applications. BGs have in fact the ability to form a strong bond with both hard and soft tissues once in contact with biological fluid. The enhanced interaction of BGs with the biological environment is based on their significant surface bioreactivity. This surface effect of BGs is, on the other hand, problematic for cell biology studies by standard (static) cell culture methods: an excessive bioreactivity leads in most cases to a rapid and dramatic increase of the pH of the surrounding medium, which results in cell death and makes cell culture tests on BG samples impossible. The BG research community has been aware of this for many years and numerous pre-treatments have been proposed by different groups worldwide to limit this problem. For the first time, we have reviewed in this paper the variety of surface preconditioning treatments that have been put forward over the years, we provide a summary of such pre-treatments used in laboratory practice, discussing and offering criteria that can be used for the determination of the optimal pre-treatment depending on BG composition and morphology of the sample tested (bulk, particulate, scaffolds). The information and discussion provided in this review should support best research practice when testing bioactive glasses in cell culture.